Total Antioxidant Capacity, Total Oxidant Status and Oxidative Stress Index in Rats Exposed to Extremely Low Frequency Magnetic Field - Sert1, Cemil; Deniz2, Mustafa (Asian Journal of Chemistry, 2011)
The aim of this study is to investigate the effects of a low frequency (50 Hz), low intensity (0.25 mT) magnetic field on oxidative stress of male rats. The effects of a 0.25 mT, 50 Hz magnetic field on the total antioxidant capacity, total oxidant status and oxidative stress index in male rats were investigated. In this study, 45 male rats were introduced and were divided into three groups as sham, control and experimental group. Experimental group was exposed to 50 Hz, 0.25 mT magnetic field for 14 days, 3h/d. Total antioxidant capacity, total oxidant status and oxidative stress index levels of each subject was determined. Total antioxidant capacity in exposed group was found to be decrease. But, this decrease was not statistically significant. Total oxidant status and oxidative strress index levels in the exposed group were found as increased. But, this increase was not statistically significant (p > 0.05). Control group and sham group; sham group and exposed groups were compared with each others. Statistical analysis was done by Mann-Whitney U test using SPSS 11.5 program in computer. The magnetic field generated in environmental magnetic field and by our home appliances and by industrial electrical apparatus and caused a few changes in oxidative system of rats. But, this change is not statistically significant.